The invention of Hugo Cabret : a novel in words and pictures - Selznick, Brian. (Scholastic Press, 2007)
When twelve-year-old Hugo, an orphan living and repairing clocks within the walls of a Paris train station in 1931, meets a mysterious toyseller and his goddaughter, his undercover life and his biggest secret are jeopardized.